HIECS: Data accuracy & extracting indicators - El lethiy, Heba (2018)
as part of the IFPRI-Egypt Seminar Series- funded by the United States Agency for International Development (USAID) project called “Evaluating Impact and Building Capacity” (EIBC) that is implemented by IFPRI.